1987
DOI: 10.1523/jneurosci.07-12-03888.1987
|View full text |Cite
|
Sign up to set email alerts
|

The role of dopamine in intracranial self-stimulation of the ventral tegmental area

Abstract: The role of dopaminergic (DA) neurons in brain stimulation reward produced by electrical stimulation of the ventral tegmental area (VTA) was investigated in the rat. In the first experiment, extensive 6- hydroxydopamine lesions of the ascending fibers of the mesotelencephalic DA projections resulted in significant changes in intracranial self-stimulation (ICS) rate-current intensity functions when the lesion was ipsilateral to the stimulating electrode. Similar contralateral lesions had no effect on these func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(76 citation statements)
references
References 35 publications
4
69
0
3
Order By: Relevance
“…These animals also consistently exhibited higher maximal response rates during self-stimulation tests. Collectively, these novel results extend previous demonstrations of the involvement of the hippocampal formation in motor output and rewarded behavior [5,9,17,24,48,49] by demonstrating that lesions of this structure can dramatically alter behaviors traditionally ascribed to the mesoaccumbens DA system [2,13,14,29,[43][44][45].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These animals also consistently exhibited higher maximal response rates during self-stimulation tests. Collectively, these novel results extend previous demonstrations of the involvement of the hippocampal formation in motor output and rewarded behavior [5,9,17,24,48,49] by demonstrating that lesions of this structure can dramatically alter behaviors traditionally ascribed to the mesoaccumbens DA system [2,13,14,29,[43][44][45].…”
Section: Discussionsupporting
confidence: 82%
“…This was accomplished by using an intra-cranial self-stimulation (ICSS) paradigm, in which the mesolimbic DA system was directly activated by stimulation of the ventral tegmental area (VTA). It has been demonstrated that electrical brain stimulation of the VTA potentiates DA release in the NACC [13,14,[43][44][45]. Electrochemical analyses have revealed that VTA stimulation induced DA release in the NACC increases as a function of increasing current intensity [2].…”
Section: Introductionmentioning
confidence: 99%
“…Examples are changing visual images, movies, and sexual pictures for which monkeys are willing to exert effort and forego liquid reward (53,124), and the ever increasing prices of paintings (fame and pride may contribute to their reward value). Not surprisingly, the first animal studies eliciting approach behavior by electrical brain stimulation interpreted their findings as discovery of the brain's pleasure centers (398), which were later partly associated with midbrain dopamine neurons (103,155) despite the notorious difficulties of identifying emotions in animals.…”
Section: Reproductionmentioning
confidence: 99%
“…The effect is partly based on activation of VTA and SNpc dopamine neurons (103,155) and involves dopamine release onto D1 receptors in nucleus accumbens (117). Optogenetic activation of midbrain dopamine neurons in rodents elicits learning of place preference, nose poking and lever pressing, and restores learning in a blocking procedure (FIGURE 19, B-D) (2,244,271,562,605,641).…”
Section: Sufficient Dopamine Involvement In Learning (Stimulation)mentioning
confidence: 99%
“…An impressive number of studies using a variety of methodological approaches, have established that the mesolimbic dopamine (DA) pathway is critically involved in reward function (for reviews, see [4] and [29]). Three distinct behaviors that have been used to assess reward processes are intracranial self-stimulation [ 3,5,7,21 ], drug self-administration [23,24,30,32] and drug-induced place conditioning (for a review, see [27]). These behaviors have been shown to be altered following dopamine manipulations.…”
Section: Introductionmentioning
confidence: 99%